IMPROVING THE QUALITY OF STUDENT SOFT SKILLS THROUGH INTERNSHIPS TO REDUCE THE NUMBER OF EDUCATED UNEMPLOYED - Baby Poernomo; Avradya Mayagita (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Internships are training activities or courses carried out by students to improve their soft skills competencies. Internship conducted by students can not only provide benefits to students who take part internship program, but with internship activities students can also improve their soft skills competency. This is a qualitative research with a phenomenological approach. Data collection was carried out using semi-structured interviews with students who had completed internships in private companies and government institutions. The research results show that internship activities carried out by students are a good means to improve their soft skills competencies, especially in terms of behavior, communication, critical thinking skills, ability to work in teams, desire to continue learning, service and entrepreneurship skills, ethics and leadership. The success of interns in improving the quality of their soft skills also depends on their willingness to continue learning from experience and from the mistakes they make. If students can improve their soft skill competencies optimally, then this can help reduce educational unemployment.